Role of early childhood educators professionalism in managing learning activities in RA Uniq Kota Pekanbaru - Raihana Raihana; Dian Tri Utami; Arya Antony Putra (Universitas Ahmad Dahlan, 2020)
Learning management process in early childhood classroom is inseparable from the early childhood educators’ professional role in creating a learning atmosphere, managing learning process, implementing learning strategies, providing learning media and learning model that are able to create a conducive, safe, and comfortable learning atmosphere. Good curriculum and learning management plan are likely to fail to meet their goals when teachers could not perform their professional role well. In RA Uniq, teachers’ professional role is pivotal in supporting the learning plan and management. The present study aimed to explore the role of early childhood educators’ professionalism in managing the learning process in RA Uniq To this end, five participants were recruited, consisting of four teachers as the main informant and the head of RA uniq as additional informant. The present study applied qualitative method, the data were collected using interview, observation, and documentation. This study revealed that early childhood educators in RA Uniq played some professional role in managing the learning process, namely as facilitator, motivator, inspirator, model, and a caregiver